Antifungal Activities of Pure and ZnO-Encapsulated Essential Oil of Zataria multiflora on Alternaria solani as the Pathogenic Agent of Tomato Early Blight Disease - Akhtari, Arezou; Davari, Mahdi; Habibi-Yangjeh, Aziz; Ebadollahi, Asgar; Feizpour, Solmaz (Frontiers in Plant Science, 2022)
The utilization of plant essential oils (EOs) and nanomaterials due to their safety compared with synthetic chemicals, has been considered in plant diseases management. In this study, the inhibitory effect of Zataria multiflora, Nepeta haussknechtii, Artemisia sieberi, and Citrus aurantifolia EOs in pure and ZnO nanocapsulated formulations were evaluated on the mycelial growth of Alternaria solani to find a suitable alternative for synthetic chemicals. The crystal structure and morphological properties of the fabricated nanomaterials were assessed via XRD (X-ray diffraction) and SEM (scanning electron microscope) analyses. The textural features of the prepared nanoparticles were investigated with BET (Brunauer-Emmett-Teller) analysis, and the presence of elements in the samples were studied with EDX (energy dispersive X-ray) technique. The mycelial growth inhibitory (MGI) was performed in the laboratory by mixing with PDA medium at concentrations from of 100, 300, 600, 1,000, 1,500, and to 2,000 ppm. Based on the results, major differences were monitored between different concentrations. At the highest studied concentration, the inhibition of Z. multiflora EO was 100%, which was 43.20%, 42.37%, and 21.19% for N. haussknechtii, A. sieberi, and C. aurantifolia, and the inhibition of their nanocapsules were 100%, 51.32, 55.23, and 26.58%, respectively. In the greenhouse study, Z. multiflora EO and its nanocapsule (ZnO-ZmEO) were compared with the ZnO and chlorothalonil fungicide based on the highest inhibitory of Z. multiflora in vitro. The highest antifungal effect was related to the ZnO-ZmEO with 53.33%. Therefore, the ZnO-ZmEO formulation can be recommended as a bio-fungicide for managing and controlling of tomato early blight disease after further research.